Hong Kong’s Stand-off: Indigenous Dynamics and International Perspective - A. I. Salitskii (Ассоциация независимых экспертов «Центр изучения кризисного общества» (in English: Association for independent experts “Center for Crisis Society Studies”), 2021)
In February 2019, Administration of Hong Kong initiated Extradition Bill, which sparked mass protests in June. The scale of the protests was unprecedented in the history of the SAR and resulted in violent clashes between police force and young radicals organized by ‘localist’ groups. The authors present a short history of interaction between pro-Beijing and pan-democratic camps in the territory concentrated on the reform of the election system of the SAR. They conclude that exacerbation of the political stand-off in Hong Kong started in 2007 when the authorities promised a possible transit to universal suffrage in 2017. The demands for this transit were not satisfied in 2014 leading to ‘Umbrella revolution’ – the first manifestation of radical youth movements. Detecting the causes of the conflict the authors look into the concept of ‘Hong Kong identity’ as opposed to ‘Chinese identity’ popular in sociological studies of the public opinion in the SAR. They try to investigate other reasons for the growing distress and protests of young generation of Hongkongers, both indigenous and exogenous. The latter correlate strongly with a general trend towards deterioration in Sino-American relations. A wide picture showing interference of the US in Hong Kong’s political life and instigation of protests in 2019-2020 is presented. In the stormy 2020, however, political situation in Hong Kong became more stable following adoption of the Law on Safeguarding National Security in the Hong Kong by the China’s parliament in late June. Closing some loopholes in the SAR legislation the Law facilitates the fight with radical groups. Still, a major healing in interaction of pan-democrats and loyalists is ahead to address gloomy economic and social situation in the territory.